2004
DOI: 10.1111/j.1365-2389.2004.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic sulphate extraction from SO2‐impacted Andosols

Abstract: Sulphate sorption on to the surface of short-range ordered minerals and precipitation of Al-hydroxy sulphate contribute to the acid neutralizing capacity of soils. The correct measurement of total inorganic sulphate is thus essential in soils that are accumulating SO 4 2-anions. We extracted SO 4 2-by various solutions, namely 0.005 M Ca(NO 3 ) 2 , 0.016 M KH 2 PO 4 , 0.5 M NH 4 F and 0.2 M acidic NH 4 -oxalate (pH 3), from Vitric and Eutric Andosols exposed to prolonged deposition of acid and SO 2 from an act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 30 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Finally, S contents (not shown) ranged between 0.1 and 0.5 g kg − 1 in the clay fraction. Most probably, this element should appear as sulphate anion likely sorbed onto colloidal surfaces of iron oxides (Delfosse et al, 2005). The carbon loss in the liquid volume (L) used for dispersion was actually moderate, as it ranged between 1 and 15% of total C content, and was generally below 6%.…”
Section: Soil Physico-chemical Propertiesmentioning
confidence: 99%
“…Finally, S contents (not shown) ranged between 0.1 and 0.5 g kg − 1 in the clay fraction. Most probably, this element should appear as sulphate anion likely sorbed onto colloidal surfaces of iron oxides (Delfosse et al, 2005). The carbon loss in the liquid volume (L) used for dispersion was actually moderate, as it ranged between 1 and 15% of total C content, and was generally below 6%.…”
Section: Soil Physico-chemical Propertiesmentioning
confidence: 99%
“…occlusion (Delfosse et al, 2005a). Although most of the inorganic SO 4 2− in these soils tends to be retained by an adsorption mechanism, precipitation also may contribute to SO 4 2− sorption for a significant part (Prietzel and Hirsch, 2000;Delfosse et al, 2005a,c).…”
Section: Introductionmentioning
confidence: 95%
“…The Andisols of Masaya Volcano receive continuous inputs of SO 2 gas (200-700 mg m − 2 day − 1 ; Delmelle et al, 2001). Delfosse et al (2005a) suggested that this SO 2 promotes Al-hydroxy sulfate precipitation as a result of enhanced weathering caused by strong acid loading and the large sulfate concentrations in soil solutions.…”
Section: Introductionmentioning
confidence: 98%
“…Among the newly proposed solvents for determining sulfates, oxalate and NH 4 F do not have the risk of converting organic S into inorganic S (Prietzel and Hirsch, 2000;Delfosse et al, 2005a). Delfosse et al (2005a) showed that compared to NH 4 F, oxalate extracted more inorganic sulfates from Andosols.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation